2002
DOI: 10.1046/j.1365-2141.2002.03959.x
|View full text |Cite
|
Sign up to set email alerts
|

Fludarabine, cyclophosphamide and mitoxantrone in the treatment of resistant or relapsed chronic lymphocytic leukaemia

Abstract: Summary. We evaluated the efficacy and toxicity of fludarabine combined with cyclophosphamide and mitoxantrone (FCM) in patients with relapsed or resistant chronic lymphocytic leukaemia (CLL). In total, 37 patients with recurrent or resistant CLL received FCM: fludarabine 25 mg/m2 intravenously (IV), d 1–3; cyclophosphamide 200 mg/m2 IV, d 1–3; and mitoxantrone 6 mg/m2 IV, d 1, at 4‐week intervals for up to six courses. Moreover, 23 patients received FCM with cyclophosphamide 600 mg/m2 i.v. and mitoxantrone 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
1
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(140 citation statements)
references
References 35 publications
5
128
1
6
Order By: Relevance
“…The majority of patients treated with the FCR regimen [27] for relapsed CLL experienced grade III-IV neutropenia (89%), which was complicated by neutropenic fever in 12% of the patients. Because of the presence of adverse events, approximately 50% of refractory patients treated with fludarabine combination regimens need to have dose reductions, skip courses of treatment, or have delays in administration of therapy because of myelosuppression [30,31], while our patients completed the planned 4 R-BAC cycles in 69% of cases with only 9% of cycles that were delayed. The RB regimen was associated with severe infections in 12.8% of patients, in front of a Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients treated with the FCR regimen [27] for relapsed CLL experienced grade III-IV neutropenia (89%), which was complicated by neutropenic fever in 12% of the patients. Because of the presence of adverse events, approximately 50% of refractory patients treated with fludarabine combination regimens need to have dose reductions, skip courses of treatment, or have delays in administration of therapy because of myelosuppression [30,31], while our patients completed the planned 4 R-BAC cycles in 69% of cases with only 9% of cycles that were delayed. The RB regimen was associated with severe infections in 12.8% of patients, in front of a Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of CLL, which had largely been based on the use of alkylating agents, is currently switching to purine analogs-based regimens with or without monoclonal antibodies. [2][3][4][5][6] These combinations induce higher response rates and a longer disease-free survival than alkylating agents or fludarabine alone. 3,4 However, a significant number of patients are refractory to therapy.…”
Section: Introductionmentioning
confidence: 99%
“…29,37,60 In a number of studies, an FCM regimen (fludarabine 25 mg/m 2 per day for 3 days, cyclophosphamide 200 -300 mg/m 2 per day for 3 days, and mitoxantrone 6 -8 mg/m 2 per day for 1 day) yielded noteworthy results. 39,52,62,63 Montoto et al 63 reported an overall response rate of 95% (CR rate, 75%); in addition, 69% of all patients in that study achieved molecular remission, and the 1.5-year failure-free survival rate was 90%. These results were confirmed by Spriano et al, 39 who reported the occurrence of molecular remission in 74% of all patients.…”
Section: Fludarabine-containing Regimensmentioning
confidence: 94%
“…The response rates associated with fludarabinecontaining regimens are slightly lower for patients with recurrent FL. 30,31,36,62,64 In a randomized trial conducted by the German Low-Grade Lymphoma Study Group (GLSG), Dreyling et al 52 compared the FCM regimen with combined immunochemotherapy (FCM plus rituximab) in patients with recurrent or refractory low-grade NHL; the chemotherapy-only regimen resulted in an overall response rate of 70% and a CR rate of 23%.…”
Section: Fludarabine-containing Regimensmentioning
confidence: 99%